A documentary history of Arkansas - Williams, C. Fred; Bolton, S. Charles; Moneyhon, Carl H. (The University of Arkansas Press, 2013)
C. Fred Williams is professor emeritus of history at the University of Arkansas at Little Rock and coeditor of Understanding the Little Rock Crisis: An Exercise in Remembrance and Reconciliation.